Death of Rationality: The Social Networks' Factor in Policy Response to Ebola. Issue 12 (14th October 2016) - Elmedni, Bakry
ABSTRACT: The sociopolitical role of social networks in public decision-making is far from fully understood. Their fast-pace and elusive nature makes the situation fluid and therefore susceptible to rushed theorization. The emerging dominant view is that social networks increase mass political polarization. A new view proposes that social networks increase harmony and tolerance. By examining the role of social networks in the policy response to Ebola in the United States, this paper suggests that social networks play a dual role: increasing polarization around politically divisive issues and promoting tolerance regarding less contentious issues. The paper also expanded the definition of social networks to include online discussions forums. Using the public choice theory and its rational model as a frame of reference, the study focused on six online forums during the peak of Ebola scare, October 2014 through January 2015.